ANALYSIS OF THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS IN THE INPATIENT ROOM OF DR. R. HARDJANTO HOSPITAL, BALIKPAPAN - Vip Paramarta; Tetty Hutagaol; Ayu Laili Rahmiyati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Background: The implementation of Electronic Medical Records (EMR) at Dr. R. Hardjanto Hospital, Balikpapan aims to improve the effectiveness and quality of services. This study uses a qualitative approach with a case study, analyzing the implementation of EMR through the 5M framework: Man, Machine, Method, Money, Material. Method: Qualitative research with a case study approach was conducted in the inpatient ward. Data were collected through in-depth interviews with 16 key informants, direct observation, and documentation. Data analysis used Nvivo 15 software with data reduction, data presentation, and conclusion drawing techniques. Data validity was guaranteed through triangulation of sources and techniques . Results: The implementation of EMR has increased work efficiency and operational cost savings. However, there are still significant obstacles: (1) human resources are not fully competent, (2) network infrastructure is slow and unstable, (3) SOPs have not been fully implemented, (4) dualism of manual and electronic systems, and (5) budget limitations for device maintenance. Conclusion: The implementation of EMR provides positive benefits, but requires infrastructure improvements, intensive training, SOP revisions, and budget increases.